2000
DOI: 10.1523/jneurosci.20-08-02792.2000
|View full text |Cite
|
Sign up to set email alerts
|

Do Phosphatidylinositides Modulate Vertebrate Phototransduction?

Abstract: Mammalian rod cyclic nucleotide gated (CNG) channels (i.e., alpha plus beta subunits) are strongly inhibited by phosphatidylinositol 4, 5-bisphosphate (PIP(2)) when they are expressed in Xenopus oocytes and studied in giant membrane patches. Cytoplasmic Mg-ATP inhibits CNG currents similarly, and monoclonal antibodies to PIP(2) reverse the effect and hyperactivate currents. When alpha subunits are expressed alone, PIP(2) inhibition is less strong; olfactory CNG channels are not inhibited. In giant patches from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 40 publications
1
59
0
Order By: Relevance
“…Phosphatidylinositol 4,5-bisphosphate inhibition of sea urchin HCN channels (34) and ELK channels of the KCNH family (35) is thought to occur via the proximal AЈ helix. CNG channels have also been shown to be inhibited by phosphatidylinositol 4,5-bisphosphate (36), and it is possible that the AЈ helix is involved in this regulation. These studies indicate that the AЈ helix is a strong modulator of gating in the cyclic nucleotide-regulated channel family, and may be an important site for channel regulation in photoreceptors, olfactory receptors, and other neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphatidylinositol 4,5-bisphosphate inhibition of sea urchin HCN channels (34) and ELK channels of the KCNH family (35) is thought to occur via the proximal AЈ helix. CNG channels have also been shown to be inhibited by phosphatidylinositol 4,5-bisphosphate (36), and it is possible that the AЈ helix is involved in this regulation. These studies indicate that the AЈ helix is a strong modulator of gating in the cyclic nucleotide-regulated channel family, and may be an important site for channel regulation in photoreceptors, olfactory receptors, and other neurons.…”
Section: Discussionmentioning
confidence: 99%
“…PI-4,5-P 2 can activate phosphodiesterase, which results in the inhibition of current fl ow through cyclic nucleotide-gated channels in ROSs ( 240 ). Modulation of phototransduction gain by changes in PI levels has been reported ( 241 ).…”
Section: Phosphoinositides In Retina Structure and Functionmentioning
confidence: 99%
“…Activation of rod channels is reduced dramatically by application of diacylglycerol derivatives (22,23), all-trans-retinal (24), and phosphatidylinositol-4,5-bisphosphate (PIP 2 ) (25), and activation of olfactory CNG channels is inhibited by cholesterol depletion (26). Zhainazarov et al (11) reported that PIP 3 inhibits heterologously expressed CNGA2 homomeric channels or CNGA2͞CNGA4 heteromeric channels to nearly the same extent as native channels in olfactory sensory neuron membranes.…”
mentioning
confidence: 99%